PERLINDUNGAN HUKUM TERHADAP DATA PRIBADI PENGGUNA APLIKASI ZOOM DARI KEJAHATAN CYBER CRIME - Dita Ramadhania (Universitas 17 Agustus 1945 Samarinda, 2021)
ABSTRACT On this day, technological advances can no longer be stopped. The development of electronic information and communication systems technology becomes a new style of communication. Electronic information and communication systems play a role as a behavior changer in Indonesian society. One of the media social that is currently popular is Zoom. Within a few months, various news and cases have emerged that reveal the weakness of this application. In general, this research aims to find out Zoom Video Communications, Inc. responsibility as the organizer of the Zoom application in protecting the personal data of its users from cybercrime and protecting the personal data of users of the Zoom application from cyber crime in accordance with the applicable law in Indonesia. The type of research used in this research is normative legal research or doctrinal. The results showed that the responsibility and legal protection that given by Zoom Video Communications, Inc. is good enough, though there are still some flaws that need to be fixed.Keyword: Zoom Video Communications, Inc, Zoom Application, Cyber Crime, Privacy, Personal Data